To what extent does genetic content in textbooks contribute to scientific literacy? Analysis of STSE issues in textbooks - Florbela M. Calado; Franz-Josef Scharfenberg; Franz X. Bogner (Universidade Católica Portuguesa, 2016)
Our article analyses science-technology- society-environment (STSE) issues in the genetics-related chapters of Portuguese natural sciences and biology textbooks and considers how they contribute to students' scientific literacy. We inspected manner of imparting of the decontextualized and socially neutral view of science and technology (S&T) as an obstacle for achieving scientific literacy. Our sample comprised four textbooks, two for the 9th and two the 12th grades. We identified and content-analytically analyzed 1019 STSE statements with regard to their compliance with previously proposed criteria. We quantitatively analyzed the statements' frequencies. We noted an attempt to approach STSE issues, but we found important deficiencies in all the textbooks, as well as indicators of a distorted view of science. We discuss possible influences of the socio-cultural context in the selection of STSE contents, in the terms being applied, as well as in the S&T conceptions displayed by the textbooks.